Effects of extracorporeal shock wave assisted drug therapy on patients with temporomandibular joint disorder - WANG Pengcheng, CHEN Chunhui, TONG Xi, FU Xinhai (Kouqiang yixue)
Objective To analyze the effect of extracorporeal shock wave assisted drug therapy on clinical outcomes of patients with temporomandibular disorders (TMD). Methods A total of 86 TMD patients in our hospital from September 2018 to September 2019 were included and divided into group A (n=43) and group B (n=43) by random number table method. Group A (n=43) received oral glucosamine hydrochloride tablets on the basis of conventional treatment; group B (n=43) received extracorporeal shock wave therapy on the basis of group A. The pain degree, maximum mouth opening, temporomandibular joint function, temporomandibular joint bounce times, life quality and occurrence of adverse reactions were compared between the two groups. Results Compared with that before treatment, the visual analogue scale (VAS) scores, maximum mouth opening, temporomandibular joint dysfunction index (DI), palpation index (PI), Fricton craniomandibular index (CMI) level, joint bounce times and oral health impact scale (OHIP-14) score of two groups were significantly improved (P< 0.05), and all indexes in group B were significantly better than those in group A (P<0.05). There was no significant difference in the incidence of adverse reactions between the two groups (P>0.05). Conclusion Extracorporeal shock wave assisted drug therapy can effectively reduce joint bounce in TMD patients, relieve patients’ pain, improve patients’ life quality and temporomandibular joint function, and has good safety.